М'ясна напутня їжа в поховальному обряді Дніпро-Прутської бабинської культури - Литвиненко, Р.О. (Археологія, 2023)
У статті схарактеризовано та проаналізовано
м’ясну їжу з поховань дніпро-прутської бабинської
культури, виявлено специфіку цієї категорії в різних
її локальних варіантах, а також продемонстровано відмінності використання тварин у поховальному обряді трьох бабинських культур. In the funeral rites of many archaeological cultures of the Bronze Age of Eastern Europe, it was practiced to accompany the
deceased with the afterlife food, in particular meat, which is documented on the basis of animal bones in graves. This practice
had taken place among pastoralists who left behind the sites of the Babyne Cultural circle. Among three Babyne’s cultures, only
one — the Dnipro-Prut culture (DPBC) — lacks research on funerary meat food, which is not only an element of the burial
ritual, but also serves as an important criterion for the cultural attribution of burials. The purpose of this paper is to describe and
evaluate the informative potential of parting meat food of the DPBC. The operational arsenal of research includes methods of
statistics, correlation, planigraphy and cartography. As a result of the study, it became clear that all three local variants of the
DPBC (Dnipro-Dnister, Dnipro-Buh and Dnister-Prut) are characterised by a similar list of varieties of meat food (remains of
ribs, vertebrae, tailbone, and legs of domestic animals, mostly sheep and bulls (fig. 1; 2). Along with this similarity, there were
certain differences in the specific gravity and placement of the mentioned varieties of meat food in each local variant of the
DPBC. Moreover, there were variations in the specific gravity and placement in the grave of the food in each local variant of the
DPBC (tab. 1—4).
The given facts, on the one hand, confirm the correctness of the selection of the DPBС itself in the structure of the Babyne
cultural circle, as well as the selection of local variants in the structure of the DPBC, and on the other hand, demonstrate its difference
from two other Babyne cultures — Dnipro-Don and Volga-Don — whose burial rite was characterised by completely different
sets of bones of domestic animals (fig. 3). In addition, the meat food in the burials, in combination with other data, demonstrates
the heredity between successive cultures of the Middle—Late Bronze Age, in our case Catacomb — Babyne — Zrubna cultures.